OC-031 Outreach community testing for hepatitis C in an ethnic population. (23rd September 2015) - Jafferbhoy, H; Miller, M; McIntyre, P; Mcleod, S; Dillon, J F
Abstract : Introduction: Hepatitis C (HCV) is a leading cause of liver disease worldwide The World Health Organisation (WHO) estimates a worldwide prevalence of 170 million or 2.2%, although there is considerable geographical variation, Scotland, due to intravenous drug misuse, has higher prevalence of HCV infection compared with other European countries, estimated at 1% of the population. There is considerable ethnic diversity in Scotland, with a large Pakistani subpopulation. In Pakistan the prevalence of HCV is between 6 and 10%.1 Methods: We arranged a series of HCV awareness meetings in Mosques and Pakistani Women's Associations in Dundee. Thereafter we set up a series of sessions in the same venues offering HCV testing. Venous blood samples were taken for testing of HCV IgG and HBsAg, using the Abbott Architect system. Relevant past medical, family and travel history was also recorded as well as history of risk factors for HCV. Results: 170 people were tested, representing 10% of the Dundee Pakistani population of which 145 were male. The mean age±SD was 45.11 (16.7) years. Seven patients (4.1%) of the cohort were Anti HCV positive and five (2.9%) were PCR positive. Only two people had previous testing for HCV, although 86.5% of the cohort had attended their GP within the past 2 years. 76.5% of the cohort had resided in the UK for at least 5 years. Less than 7% of the cohort was born in the UK. Risk factors for HCV transmission were only noted in a minority of patients who were HCV positive. One of seven had a family history and two of seven had a previous injection (IM or IV) in Pakistan. None had a history of drug misuse or transfusion. Of the entire group 33.5% reported previous therapeutic injections and 10% had a previous surgical procedure carried out in Pakistan. 3.5% of the cohort had a blood transfusion. 15.2% reported a family history of HCV infection. Conclusion: This pilot project confirms that the Hepatitis C incidence in the healthy Pakistani migrant is higher than the native population. At-risk groups for HCV can be targeted for testing and treatment with outreach clinics. Using Scottish Intercollegiate Guidelines Network (SIGN) recommendations for assessing risk factors we would not have tested majority of those infected.2 Awareness needs to be raised among physicians regarding screening of ethnic populations for HCV.